Bioaccumulation of Heavy Metals in Freshwater Invertebrates of the Kallada River, India: Implications for Ecological Risk and Food Safety - Soumini, Tarunpal Chandrapal; Vijayan, Reshmi; Hameed, Byju; Hegde, Maitreyi (Asian Journal of Biological and Life Sciences)
Background: Rivers are crucial freshwater ecosystems that sustain biodiversity, livelihoods, and essential ecosystem services, but face increasing contamination from industrial, domestic, agricultural, and mining activities. Heavy metals, being non-biodegradable, persist in sediments and bioaccumulate in aquatic organisms, posing ecological and public health concerns. Materials and Methods: This study assessed heavy metal contamination in the Kallada River and connected sites in Kollam district by analyzing water, sediment, and tissues of freshwater invertebrates (crabs, shrimps, prawns, bivalves, and aquatic insects). Invertebrates were selected as bioindicators because of their sediment association and metal accumulation potential, metals, thereby providing time-integrated evidence of contamination. Trace metals (Ni, Cu, Zn, As, Cd, and Pb) were quantified using ICP MS. Results and Discussion: While water and sediment metal levels were within WHO and ISQG guideline values, bioaccumulation was evident, particularly at downstream sites, with species-specific uptake influencing the Metal Pollution Index (MPI). Spatial variations in MPI showed peak contamination in Site A, crabs and shrimps at Site B, and prawns at Site C, with prawns at Site C exhibiting the highest MPI (15.4). Conclusion: These findings highlight the critical role of species-specific uptake in shaping ecological risk and underscore the importance of combining MPI with tissue-level metal analysis to provide a more comprehensive assessment of ecological and public health implications in aquatic environments.
Keywords: Ecotoxicology; Sediment; Trophic Transfer.